Pengaruh Gaya Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi di SMA Negeri 15 Palembang - Andini, Andini (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to analyze the effect of learning styles on student learning outcomes in Economics subjects at SMA Negeri 15 Palembang. The background of this research is the low awareness of students towards their respective learning styles, which has an impact on the difficulty of understanding Economics material and lowering academic achievement. The research method used is quantitative with a questionnaire to identify learning styles and documentation of even semester midterm results to measure learning outcomes. The study population was all grade X students, with a sample of 70 students from classes X.2 and X.3. The results showed that the dominant learning style was the auditorial style (37.14%), followed by kinesthetic (32.86%) and visual (30.00%). Based on the t test, the value of T-count = 6.003> T-table = 1.668 was obtained. Furthermore, the significant value of 0.000 <0.05 means that the significant value is smaller than 0.05. From this it can be said that in this study Ha is accepted and Ho is rejected. Therefore, the hypothesis in this study is that there is a significant effect of learning styles on student learning outcomes at SMA Negeri 15 Palembang.